Gouvernance de l’orpaillage dans le domaine de chasse de Bili-Uéré : entre application de la règlementation nationale et nécessités locales de survie dans la Province du Bas-Uélé en République démocratique du Congo - Justin Kyale Koy; Gloire Ganza Bamulezi; Matthieu Mamiki Kebongobongo; Serge Alebadwa Mombenga; Antoine Tabu; Jean-Claude Kalala; Camille Welepele; Theodore Tréfon; Elie Lamarre (VertigO)
The governance of artisanal gold panning is characterized, in most African countries, by informal practices. The Bili-Uéré Hunting Domain (DCBU), the largest protected area in the Democratic Republic of Congo (60,000 km2), is threatened by artisanal gold mining, the governance of which deserves to be questioned. This article aims to demonstrate how local survival requirements limit the application of national legislation in the governance of gold panning in the said area. To achieve this, data collection mobilized a triple input of methodological instruments including documentation, discourse (individual and group interviews) and direct observation. At the end of the data analysis, the results show that the governance of gold panning in the DCBU is characterized by a coexistence between national regulations and informal practices. This coexistence is due to the local socio-economic needs of the stakeholders, abandoned by the State in its sovereign functions. The actors involved in the governance of gold panning have thus developed systems of relationships around the issues linked to this activity. These results prove that the question of gold panning governance in the DCBU is complex because the stakeholder games are defined at all levels, notably national, provincial and local. At each of these levels, gold panning is based on very structured local governance, governed by the predominance of informal rules. A holistic response from the State and other stakeholders is therefore necessary to reconcile socio-economic concerns with the application of mining and forestry regulations.